(untitled) (African Human Mobility Review, 2021)
The relationship between migration and health is complex, and its impact varies considerably among individuals, across migrant groups, and from country to country. Although African immigration to the United States (U.S.) and South Africa has increased rapidly over the past two decades, little is known about the health experiences of this growing population even though conditions surrounding the migration process have been found to increase vulnerability to ill health. The aim of this study is to examine and compare the perceptions of African refugees and immigrants to South Africa and the U.S. on informational support and its impact on health status. Data was collected from purposively selected 62 African immigrants to the United States and 66 African immigrants to South Africa using the PROMIS Global Health v1.2 and the PROMIS Item Bank v2.0 (informational support) instruments which assess an individual’s general physical, mental and social health.